46,XX Differences of Sex Development outside congenital adrenal hyperplasia: pathogenesis, clinical aspects, puberty, sex hormone replacement therapy and fertility outcomes - Stancampiano, Marianna Rita; Meroni, Silvia Laura Carla; Bucolo, Carmen; Russo, Gianni (Frontiers in Endocrinology, 2024)
The term ‘differences of sex development’ (DSD) refers to a group of congenital conditions that are associated with atypical development of chromosomal, gonadal, and/or anatomical sex. DSD in individuals with a 46,XX karyotype can occur due to fetal or postnatal exposure to elevated amount of androgens or maldevelopment of internal genitalia. Clinical phenotype could be quite variable and for this reason these conditions could be diagnosed at birth, in newborns with atypical genitalia, but also even later in life, due to progressive virilization during adolescence, or pubertal delay. Understand the physiological development and the molecular bases of gonadal and adrenal structures is crucial to determine the diagnosis and best management and treatment for these patients. The most common cause of DSD in 46,XX newborns is congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency, determining primary adrenal insufficiency and androgen excess. In this review we will focus on the other rare causes of 46,XX DSD, outside CAH, summarizing the most relevant data on genetic, clinical aspects, puberty and fertility outcomes of these rare diseases.